2021
DOI: 10.22190/fume210711062z
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Suitability-Feasibility-Acceptability (Sfa) Strategy With the McDm Approach

Abstract: Suitability-Feasibility-Acceptability (SFA) is a fundamental tool for the development and selection of strategy. Any type of decision-making problem can be resolved by Multiple Criteria Decision Making (MCDM) methods. In this research, we explore the complexity of determining the proper goal market for the Chilean fish market. This study proposed a combined approach of SFA with MCDM methods in a real case study. The proposed structure helps to assign the best market for Chilean export fish to West Asia. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Hashemkhani Zolfani et al [72], to remove these shortages, proposed that SFA is combined with the MCDM methods. They used the BWM method for weighing and the MARCOS method for ranking options.…”
Section: Improved Sfa Strategymentioning
confidence: 99%
“…Hashemkhani Zolfani et al [72], to remove these shortages, proposed that SFA is combined with the MCDM methods. They used the BWM method for weighing and the MARCOS method for ranking options.…”
Section: Improved Sfa Strategymentioning
confidence: 99%
“…The method determines the utility functions of the options with the help of ideal and non-ideal solutions. Scholars have successfully employed MARCOS in various areas [82][83][84]. The following steps are portrayed in IF-MARCOS for making decisions [9].…”
Section: Intuitionistic Fuzzy Marcos (If-marcos)mentioning
confidence: 99%
“…In recent years, fast technological changes, the appearance of new markets, and changing customer needs and expectations have resulted in fierce competition on the market worldwide [1]. In parallel with that energy is becoming more and more valuable because of its depletion, and as planet pollution is one of the major concerns of today's world, everyone should do their part in trying to minimize the contamination of the world that we live in.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they thoroughly investigated energy consumption in manufacturing processes (for example, trends on how materials and energy resources are used in manufacturing). Duflou et al [6] suggested that the environmental impact of manufacturing industry can be reduced in two ways: (1) by developing energy-efficient machines or (2) optimizing existing machining processes. The development of energyefficient machines entails changing the design of the machine tool, for which lot of financial resources are needed.…”
Section: Introductionmentioning
confidence: 99%